Toxicity evaluation and nasal mucosal tissue deposition of dexamethasone-infused mucoadhesive in situ nasal gelling systems - Preeti Pandey; Saurabh Pandey; Peter J. Cabot; Benjamin Wallwork; Benedict J. Panizza; Harendra S. Parekh (Elsevier, 2019)
To demonstrate safety of a developed intranasal dexamethasone-infused in situ gelling formulation, quantification of a validated clinical biomarker indicative of cytotoxic potential using a human sinonasal explant model was first confirmed. Systematic cytotoxicity studies using the lactate dehydrogenase (LDH) detection assay revealed no elevation from baseline, in LDH levels, with tissue integrity of explanted human nasal mucosa also maintained; this was further corroborated using tissue histopathological examination. Next, with safety confirmed ex vivo, freshly excised human nasal tissue was utilised to quantify dexamethasone release from the lead sol-gel systems; this being achieved through development and validation of a HPLC-UV analytical method, which reliably quantified controlled therapeutic release and deposition into mucosal tissue. Collectively, these findings indicate promise in the safety of each excipient within the concentrations employed in the functional sol-gel system, complemented by successful and reliable drug release and deposition into human nasal mucosal tissue. These findings pave the way for application of the dexamethasone-based sol-gel system to the extended delivery of corticosteroids to nasal mucosa in the management of localised inflammatory conditions of an acute and chronic nature, such as chronic rhinosinusitis, which can be expected to benefit from controlled and extended drug delivery characteristics imparted by appropriately engineered in situ gelling systems. Keywords: Intranasal soluble gels, Sinusitis, Explant human nasal mucosa, Tissue toxicity, LDH assay, Drug deposition in human nasal mucosa